Habeas corpus and parole granting. Supreme Court recent jurisprudence - Lizama Allende, Felipe (Derecho Público Iberoamericano, 2018)
This work seeks to show the test performed by the Chilean Supreme Court when it granted the claims presented to it via the constitutional habeas corpus remedy, reverting decisions that would not grant the parole benefit. There are several legal and factual grounds that the Supreme Court has considered to grant this parole decisions, which confirms the operational and active nature of the habeas corpus.